The Internalization of Moral Values in the Teaching of Adabul ‘Alim wal Muta‘allim among Second-Year MAPK Female Students at Al-Risalah Batetangnga Islamic Boarding School - Nurul Fitriani Hasan; Sudirman Sudirman; Nurzamsinar Nurzamsinar (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study examines the internalization of moral values through the teaching of the book Adabul ‘Alim wal Muta‘allim among second-year MAPK female students at Al-Risalah Batetangnga Female Islamic Boarding School. The study is grounded in the importance of moral education in shaping students’ character amid the decline of moral values among learners. It aims to describe the process of internalizing moral values and to identify the supporting and inhibiting factors in the learning process. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings show that the internalization process occurs through value transformation, value transaction, and transinternalization in learning activities, and is strengthened through habituation, exemplary conduct, social interaction, and the religious culture of the pesantren.